2015
DOI: 10.17812/blj2015.32.21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oil richness or technological characteristics of introduced varieties and local types of olive trees (Olea europaea L.) grown in Ouazzane areas (Northern Morocco)

Abstract: For the majority of local and foreign varieties, Moroccan Picholine and oleasters types, the obtained oil content relating to the fruit fresh weight varied between 14.3% to 23%; excepted, the Picual variety, type oleastre BM2, Manzanille and Cucco varieties and Moroccan Picholine M1 type, which gave oil contents higher than 23%, respectively 23.23%; 23.76%; 23.83%; 25.14% and 25.83% compared to other cultivars. Gordal, Ascolana Dura, and Bouchouk Rkike Varieties, have given average oil content relative to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
2
1
0
1
Order By: Relevance
“…In contrast with Ca content, fruit fresh weight enhanced as a result of T1 application compared to that of fruit produced under control conditions (CT). Our results are in accordance with those recorded by Kartas et al [29], indicating a negative correlation between fruit weight and Ca content.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast with Ca content, fruit fresh weight enhanced as a result of T1 application compared to that of fruit produced under control conditions (CT). Our results are in accordance with those recorded by Kartas et al [29], indicating a negative correlation between fruit weight and Ca content.…”
Section: Discussionsupporting
confidence: 94%
“…As for the shape of the fruits, it differed between spherical for the Cevellano variety, oval for the Koroneiki variety, and elongated for the other varieties under study. These results are in general agree with those obtained previously by Matouk, et al, 2007;Al-Menaie, et al, 2014;and Kartas, et al, 2016. The data presented in Table 3 shows the characteristics of the fleshy part of olive fruits, where it showed highly significant difference among some varieties for the measured characteristics of the fleshy part, where the highest average thickness of the fleshy part was 3.0 cm of the Ascolano variety, with significant differences from the rest of the varieties, while the lowest average thickness of the fleshy part was for the fruits of the Manzanillo variety which reached 0.25 cm, and there were no significant differences between it and the Koroneiki and Cevellano varieties, for which the thickness of the fleshy part reached 0.34 cm, and 0.29 cm, respectively.…”
Section: Morphological Traits Of the Olive Fruitssupporting
confidence: 93%
“…Similarities and differences (in terms of morphological and agronomical characteristics) among promising selected Moroccan autochthonous and recently introduced olive varieties are, to date, well established [ 12 , 14 , 15 ]. Researches characterizing oils obtained from these varieties have mostly focused on their quality parameters evaluation, although some studies can be also found regarding genetic, environmental and technological factors influencing the quality of these oils, and their fatty acids and triacylglycerols composition [ 7 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, to the best of our knowledge, there are no studies evaluating the nutritional value of these oils.…”
Section: Introductionmentioning
confidence: 99%